¡Qué buena leche! - Gastañaduy, Alfonso (1995)
This case study deals with the strategy designed by a company to introduce a mass consumer product to the market. It describes all the steps followed in reality to apply the decisional marketing tools. To do this, it shows the contrast between the classic sales approach followed by the company that "rests on its laurels" and that of an aggressive, dynamic company with a clear strategic marketing focus. He recommends also discussing the use of market opportunities that are sometimes so obvious that they are not "seen", and the importance of using market information to optimize decisions.